Dynamics and drivers of customer engagement: within the dyad and beyond. (24th May 2018) - Fehrer, Julia A.; Woratschek, Herbert; Germelmann, Claas Christian; Brodie, Roderick J.
Abstract : Purpose: The purpose of this paper is to extend existing engagement research in two directions: first, it operationalizes the dynamic nature of the engagement process within a customer-brand dyad and, second, it tests the interrelationships with other network actors in a triadic network setting. Design/methodology/approach: A 2×2 experimental design models the iterative nature of the engagement process based on repeated measures at three points in time, considering the contextual effects of connections with other customers and crowding-in effects based on monetary incentives. Findings: This research demonstrates that in a utilitarian service setting, customer engagement does not emerge per se in the dyadic interaction between the customer and the brand. For high levels of engagement behavior to occur, incentives and ties to other network actors are essential. Further, the findings suggest a non-linear relationship between engagement behavior and its antecedents and consequences: engagement behavior must overcome a certain intensity threshold to unfold its effect. Research limitations/implications: Further research is needed to explore the dynamic nature of the engagement process in experiential and interactive service settings, and more complex network settings that may involve more actors and more complex relationships. Practical implications: By facilitating connections between customers and compensating for low intrinsic interest, managers can facilitate actual engagement behavior even in utilitarian service contexts. Once engagement behavior has been triggered, an increased engagement disposition, higher satisfaction, higher involvement and higher loyalty follow. Originality/value: This study empirically tests the dynamic nature of the engagement process within and beyond the dyad, and has revealed a non-linear pattern of customer engagement behavior within its nomological network.